Labor resistance and municipal power: Scalar mismatch in the Los Angeles Green New Deal. (October 2022) - Furnaro, Andrea; Kay, Kelly
Abstract: In 2019, the Mayor of Los Angeles announced the Los Angeles Green New Deal (LAGND), an ambitious plan to shift the city's power system to 100% renewables by 2045. The Los Angeles Department of Water and Power (LADWP)—the electricity provider for the city and the largest municipally-owned utility in the United States—began a consultation process with local stakeholders and energy system modelers to determine possible scenarios to accomplish this goal. While the LAGND was lauded by environmentalists and progressives both within Los Angeles and beyond, it has been heavily opposed by the IBEW 18, the union that represents nearly all employees at LADWP. IBEW 18 has staged protests, created political advocacy organizations, and funded anti -decarbonization political candidates. This paper draws on 20 semi-structured interviews and other secondary materials to understand the union's oppositionand to demonstrate some of the unique challenges that municipal-scale Green New Deal (GND) plans face. We argue that the tensions between the mayor's office and unionized utility workers can be explained, at least in part, by three instances of scalar misalignment—or mismatch—that arise from trying to undertake a GND plan at the city level. These include mismatch between: (1) the scales of political activism and engagement between the mayor and the union, (2) the aims of the GND narrative and the limits imposed by the jurisdiction of the City of Los Angeles, and (3) the current and future geographies of the electric power system and related infrastructure and its path dependencies.